2006
DOI: 10.1111/j.1462-2920.2005.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Mycobacterium community and polycyclic aromatic hydrocarbons (PAHs) among different size fractions of a long‐term PAH‐contaminated soil

Abstract: Summary Mycobacterium is often isolated from polycyclic aromatic hydrocarbon (PAH)-contaminated soil as degraders of PAHs. In model systems, Mycobacterium shows attachment to the PAH substrate source, which is considered to be a particular adaptation to low bioavailability as it results into increased substrate flux to the degraders. To examine whether PAH-degrading Mycobacterium in real PAH-contaminated soils, in analogy with model systems, are preferentially associated with PAH-enriched soil particles, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 59 publications
4
76
2
1
Order By: Relevance
“…And, the ratios of abundances of different PAH-degrading genes to bacterial 16S rRNA gene in some DOM-treated soils were significantly higher than that in the control on some incubation time. It indicated that addition of DOMs was an important driving force to stimulate the growth of bacteria especially those responsible for the [35][36][37][38]. The profiling analysis of microbial communities can contribute to identify the members of potential PAH-degrading microbial consortia and understand the patterns of microbial responses to external stimuli in polluted soils [14,39].…”
Section: Discussionmentioning
confidence: 99%
“…And, the ratios of abundances of different PAH-degrading genes to bacterial 16S rRNA gene in some DOM-treated soils were significantly higher than that in the control on some incubation time. It indicated that addition of DOMs was an important driving force to stimulate the growth of bacteria especially those responsible for the [35][36][37][38]. The profiling analysis of microbial communities can contribute to identify the members of potential PAH-degrading microbial consortia and understand the patterns of microbial responses to external stimuli in polluted soils [14,39].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cells of Rhodococcus or Cryptococcus would preferentially be located in less affected microsites, as it was the case for POM, sand or silt. Niche preference for clay within a soil matrix has, in fact, been demonstrated for a Mycobacterium degrading polycyclic aromatic hydrocarbons (Uyttebroek et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The pH at the column effluent was regularly verified using pH-indicator strips (Universal indicator, Merck). DNA was extracted from 400 µL of liquid sample or 400 µg of wet solid phase as described by Uyttebroek et al (2006). Quantification of Dehalococcoides numbers was performed using real-time PCR as described previously (Dijk et al 2008) with a detection limit of 1.6×10 6 16S rDNA copies L -1 .…”
Section: Analytical Methods and Data Analysis Tcementioning
confidence: 99%